1996
DOI: 10.1136/hrt.75.4.363
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac hypertrophy as a result of long-term thyroxine therapy and thyrotoxicosis.

Abstract: Design-Cross sectional study of patients prescribed thyroxine long term (n = 11), patients with thyrotoxicosis studied at presentation (n = 23), compared with controls (n = 25); longitudinal study of patients with thyrotoxicosis studied at presentation and serially after beginning antithyroid drug treatment (n = 23). Methods-24 h ambulatory monitoring of pulse and blood pressure, echocardiography, forearm plethysmography, and autonomic function tests. Results-Long-term thyroxine treatment in doses that reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
61
0
5

Year Published

2000
2000
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(69 citation statements)
references
References 31 publications
2
61
0
5
Order By: Relevance
“…Eleven of 17 subjects in group I were affected by multinodular goiter and the other 6 were affected by solitary thyroid nodule. Stable endogenous subclinical hyperthyroidism diagnosis was confirmed in all 17 patients of group I by screening for antithyroid peroxidase (anti-TPO) and anti-thyroglobulin (anti-Tg) antibodies once and by measuring TSH, fT 4 and fT 3 twice more within the following two months. Three dimensional ultrasound examination of thyroid tissue was performed for all subjects.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eleven of 17 subjects in group I were affected by multinodular goiter and the other 6 were affected by solitary thyroid nodule. Stable endogenous subclinical hyperthyroidism diagnosis was confirmed in all 17 patients of group I by screening for antithyroid peroxidase (anti-TPO) and anti-thyroglobulin (anti-Tg) antibodies once and by measuring TSH, fT 4 and fT 3 twice more within the following two months. Three dimensional ultrasound examination of thyroid tissue was performed for all subjects.…”
Section: Methodsmentioning
confidence: 99%
“…It has been demonstrated that exogenous subclinical hyperthyroidism, in which patients treated with TSHsuppressive doses of levothyroxine, may affect the heart as in subjects with overt hyperthyroidism, but it remains controversial whether endogenous subclinical hyperthyroidism affects the heart [3][4][5].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, some authors found the increase in left ventricular myocardium mass in both overt (Nixon et al, 1979;Auer et al, 2001;Dorr et al, 2005;Marcisz et al, 2006) and subclinical (Ching et al, 1996;Biondi, 1999Biondi, , 2000Auer, 2001) thyrotoxicosis. On the other hand, there are not enough studies considering LVH occurrence in thyrotoxicosis and factors contributing its development, geometry type (eccentric or concentric), and reversibility.…”
Section: Arrhythmiasmentioning
confidence: 99%
“…The main manifestations of thyrotoxic cardiomyopathy (TCMP) are left ventricular hypertrophy (LVH) (Ching et al, 1996, Dorr et al, 2005, heart rhythm disturbances (usually, atrial fibrillation (AF)) (Dunn et al, 1986;Frost et al, 2004), dilation of the heart chambers and heart failure (HF) (Dougherty & Craige, 1973;Siu et al, 2007), pulmonary hypertension (PH) (Chu et al, 2002;Rubin & Badesch, 2006), and diastolic dysfunction. Epidemiology data on TCMP are currently lacking.…”
Section: Definition -Epidemiology Of Thyrotoxic Cardiomyopathy and Itmentioning
confidence: 99%